2008
DOI: 10.1002/ijc.24093
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality in women and men who survived the siege of Leningrad (1941–1944)

Abstract: The population of Leningrad suffered from severe starvation, cold and psychological stress during the siege in World War II in 1941-1944. We investigated the long-term effects of the siege on cancer mortality in 3,901 men and 1,429 women, born between 1910 and 1940. All study subjects were residents of St. Petersburg, formerly Leningrad, between 1975 and 1982. One third of them had experienced the siege as children, adolescents or young adults (age range, 1-31 years at the peak of starvation in [1941][1942]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 35 publications
4
56
1
1
Order By: Relevance
“…Various epidemiologic studies have indicated that psychological stress produces a significant increase in breast cancer risk, and that the nature and magnitude of the effect of stress on risk is comparable with that of other well-known risk factors for breast cancer (16). Furthermore, specific studies have suggested that the cancer-causing effects of stress may be fairly specific to the breast (17,18). We previously presented the first molecular evidence for a connection between stress and breast cancer with our observation that BRCA1 expression is repressed by the synthetic stress hormone hydrocortisone in nonmalignant mouse mammary cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…Various epidemiologic studies have indicated that psychological stress produces a significant increase in breast cancer risk, and that the nature and magnitude of the effect of stress on risk is comparable with that of other well-known risk factors for breast cancer (16). Furthermore, specific studies have suggested that the cancer-causing effects of stress may be fairly specific to the breast (17,18). We previously presented the first molecular evidence for a connection between stress and breast cancer with our observation that BRCA1 expression is repressed by the synthetic stress hormone hydrocortisone in nonmalignant mouse mammary cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…13 A study of people who underwent severe starvation and psychological stress during the Siege of Leningrad found no evidence of greater mortality from respiratory cancer, prostate cancer or all cancers after adjustment for age, social characteristic, body mass index, smoking and alcohol consumption. 14 Our study is distinguished by having complete information on exposure status and follow-up for cancer incidence and death at the individual level for the entire study period. As the conditions in Denmark during and after the War were less devastating than in many other countries, the consequences of this stressful exposure could be defined and separated with earlier and later conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Among the major long-term consequences of inadequate caloric and/or nutrient intake in childhood and adolescence may be -surprising as it may seematherosclerosis and cancer. Studies among survivors of wars and natural disasters which caused long-las ng shortages of food (the siege of Leningrad during the World War II, 'The Hunger Winter' in the Netherlands in 1994 and the Great Famine in China (1959-61) showed that the prevalence of cancer in the survivors, especially those who were children or adolescents during the famine period, was significantly increased (2-3 mes) compared to control age-matched popula ons that had never experienced periods of significant caloric depriva on or starva on [1304,1305]. The same phenomenon was observed for diabetes type 2, arterial hypertension, atherosclerosis and cardiovascular disease [1306][1307][1308].…”
Section: S Snegov the Experiments Of Professor Bran Ng (1977)mentioning
confidence: 99%